2014
DOI: 10.1155/2014/312452
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Exerts Antidiabetic Effect via PTP1B and PI3K/Akt2 Signaling Pathway in Skeletal Muscle of KKAy Mice

Abstract: Background. Liraglutide (a glucagon-like peptide 1 analog) was used for the treatment of type 2 diabetes (T2DM) which could produce glucose-dependent insulin secretion. Aim. The aim was to investigate whether liraglutide could improve myofibril and mitochondria injury in skeletal muscle and the mechanisms in diabetic KKAy mice. Method. We divided the male KKAy mice into 2 groups: liraglutide group (250 μg/kg/day liraglutide subcutaneous injection) and model group; meanwhile, the male C57BL/6J mice were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
(47 reference statements)
3
15
0
1
Order By: Relevance
“…Glucose homeostasis has been shown to be tightly regulated by GLP-1, and continuous infusion with a potent GLP-1 receptor antagonist was shown to disrupt glucose tolerance [39]. Liraglutide, a long-acting GLP-1 analogue, has been shown to attenuate myofibril and mitochondria injury in skeletal muscle of patients with T2DM through PTP1B and the PI3K/Akt signaling pathway [40]. Moreover, Kanoski et al [41] reported that liraglutide reduces the expression of PTP1B, which could explain the effects of this compound on the enhancement of STAT3 phosphorylation after liraglutide-leptin co-administration.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose homeostasis has been shown to be tightly regulated by GLP-1, and continuous infusion with a potent GLP-1 receptor antagonist was shown to disrupt glucose tolerance [39]. Liraglutide, a long-acting GLP-1 analogue, has been shown to attenuate myofibril and mitochondria injury in skeletal muscle of patients with T2DM through PTP1B and the PI3K/Akt signaling pathway [40]. Moreover, Kanoski et al [41] reported that liraglutide reduces the expression of PTP1B, which could explain the effects of this compound on the enhancement of STAT3 phosphorylation after liraglutide-leptin co-administration.…”
Section: Discussionmentioning
confidence: 99%
“…Studi lain membuktikan pemberian asam asetat, asam butirat, dan asam propionat dapat menstimulasi reseptor FFAR2 dan FFAR3 sel L di kolon yang dapat menstimulasi sekresi GLP-1 (33). Lebih lanjut, pemberian liraglutide yang merupakan analog GLP-1 berpengaruh dalam meningkatkan aktivasi phosphoinositide kinase 3 kinase (PI3K) dan AKT yang akan meningkatkan translokasi GLUT4 (34).…”
Section: Gambar 1 Gambaran Ekspresi Glut4unclassified
“…1-Hydroxymethyl-abietane-p-methylbenzenesulfonate (10 4.1.8. General procedure 6: Zn/NaI-mediated reduction The solution of 1 equiv.…”
Section: General Procedures 4: T-buooh-mediated Hydroperoxide Rearrangmentioning
confidence: 99%
“…Though many anti-T2D drugs have emerged in the past decade 5,6 , traditional anti-T2D agents such as repaglinide, metformin, dipeptidyl peptidase-IV inhibitors, a-glucosidase inhibitors and glucagon-like peptide-1 agonists, and thiazolidinediones are still the most efficacious oral drugs in the first-line monotherapy of T2D 7 . It is undoubted that new insulin sensitisers will meet great needs of T2D patients 8,9 . Protein tyrosine phosphatase 1B (PTP1B) dephosphosphorylates the tyrosine-phosphorylated insulin receptor (IR) and the downstream insulin receptor substrate (IRS) to down regulate insulin transduction [10][11][12][13][14][15] . PTP1B inhibitors could potentially improve insulin sensitivity and normalise glucose levels and therefore could be a promising therapeutic strategy in the T2D patients.…”
Section: Introductionmentioning
confidence: 99%